Microfinance Interest Rate Puzzle: Price Rationing or Panic Pricing?1. (29th April 2017) - Guo, Lin; Jo, Hoje
Abstract: We examine the relation between microfinance institution (MFI) interest rates, loan loss rates, and regulations. Our results suggest that a positive and causal association exists where loan loss rates drive MFI interest rates after controlling for confounding factors. This positive association holds after accounting for potential endogeneity based on various econometric methods and quasi‐natural experiment. Although endogeneity cannot be ruled out fully, the results of our tests suggest it plays a limited role. Our results support the price‐rationing proposition that MFIs ration credit and there is unmet demand at the market‐clearing price. This positive relation is more pronounced in countries with individualistic and uncertainty avoiding cultures.